2022
DOI: 10.7759/cureus.26988
|View full text |Cite
|
Sign up to set email alerts
|

No Difference Between Anchorless and Traditional Suture Anchors in Arthroscopic Bankart Repair: A Clinical Comparison

Abstract: BackgroundShoulder instability and recurrent dislocations are common problems encountered by orthopedic surgeons and are frequently associated with a Bankart lesion. These are classically treated with either open or arthroscopic repair utilizing traditional suture anchors, though anchorless fixation techniques have recently been developed as an alternate fixation method that reduces native bone loss and has comparable pull-out strength. MethodsA retrospective review was performed at a single institution for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While we did not look specifically at postoperative ROM, the potential ROM restriction may contribute to the preference for knotless repairs. While maximizing functional outcomes is important, and the selection of anchor type may contribute to patients’ functional improvement, numerous studies have shown consistent improvements in functional outcomes for all patients undergoing arthroscopic treatment of shoulder instability regardless of the type of anchor used [ 9 , 20 - 22 ]. The current study measured postoperative function using the UEFS, which is a tool that looks at global function rather than sports-specific function.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not look specifically at postoperative ROM, the potential ROM restriction may contribute to the preference for knotless repairs. While maximizing functional outcomes is important, and the selection of anchor type may contribute to patients’ functional improvement, numerous studies have shown consistent improvements in functional outcomes for all patients undergoing arthroscopic treatment of shoulder instability regardless of the type of anchor used [ 9 , 20 - 22 ]. The current study measured postoperative function using the UEFS, which is a tool that looks at global function rather than sports-specific function.…”
Section: Discussionmentioning
confidence: 99%